(untitled) (Baghdad Science Journal, 2022)
The main purpose of this investigation is to evaluate the concentrations of six essential metals (Na+, Mg2+, K+, Ca2+, Fe2+ and Zn2+) in saffron and a farm soil using the neutron activation analysis (NAA) as a nuclear spectrometry method. The stratified random sampling method was used here. The NAA results showed the well uptake of Mg2+, K+, Ca2+, Fe2+, and Zn2+ in saffron, which is lower than the toxicity range. Based on the contamination factor and geoaccumulation index, soil contamination levels were determined uncontaminated by Zn, moderately contaminated by Na+ and Fe2+, and strongly contaminated by Ca2+, K+, and Mg2+. Results of the contamination degree and pollution load index indicated moderately/strongly soil contamination and a moderate geometric mean of the contamination index. The Na+ enrichment factor (EF) showed a minimal man-made impact on sodium enrichment. Saffron cultivation has likely caused more accumulations of Mg2+, K+, Ca2+, and Fe2+, as well as a considerable deficiency of Zn2+ in the soil, based on EFs. The biological concentration factor showed a significant zinc accumulation by the corm of saffron. There was well translocation from corm to all the aerial tissues for K+. Also, sodium adsorption ratio, exchangeable sodium percentage, pH, and electrical conductivity evaluated the non-salinity level of soil in all saffron farms.